Emerging markets in the post-liberalisation period: evidence from the raw milk market in rural Kenya - Kijima, Y.; Yamano, T.; Baltenweck, Isabelle (Oxford University Press, 2010)
Have recent reforms improved market functioning in African economies? This article examines how the raw milk market in western and central Kenya has developed after the dairy sector liberalisation in 1992 by using panel data of 862 rural households. From the late 1990s to 2004, the proportion of rural households who sold milk increased from 37 to 51%. During the same period, the proportion of households who sold milk to traders more than doubled, while it declined from 29 to 12% for those who sold milk to dairy cooperatives. On the basis of the price differentials between the farm gate and retail prices, we find that the functioning of the market improved between the late 1990s and 2004; in turn, the development of the milk market has increased the adoption of improved cows, resulting in higher milk sales.